Factors that contribute insurance fraud / Nur Hamizah Jaffar Sedik and Siti Shakila Anura Rosli - Jaffar Sedik, Nur Hamizah; Anura Rosli, Siti Shakila (2013)
Insurance fraud is any act committed with the intent to fraudulently obtain payment from an insurer. Fraudulent claims account for a significant portion of all claims received by insurers, and cost insurers and their insured billions of dollars annually. The nature and prevalence of insurance fraud has been studied only to a limited extent, even in the USA and Europe. Nevertheless, national authorities have pressed ahead with various approaches to control such fraud. This paper briefly outlines factors that contribute consumer to commit insurance fraud. The analysis sought to identify factors that contribute consumer to commit insurance fraud with respect to (a) knowledge, (b) motive and (c) attitude. The paper presents secondary data which the journal and books from the previous research conducted by others researcher. The survey was conducted and questionnaire was distributed to 110 respondents from several insurance company and brokers that selected as a sampling in this study. For dependent variable are insurance claim fraud and independent variables are knowledge, motive and attitude.